Endodontic management of taurodontic teeth - Prakash R; Chenduran Vishnu; Ballal Suma; Velmurugan N; Kandaswamy D (Wolters Kluwer Medknow Publications, 2005)
Taurodontism is a morpho-anatomical change in the shape of the tooth in which the body of the tooth is enlarged and the roots are reduced in size. Although taurodontism is a dental rarity, this unusual radicular form should merit circumspect considerations in planning and treatment. Endodontic management in taurodont teeth has been described as complex and difficult. The present paper describes the successful completion of endodontic treatment in three taurodontic teeth with appropriate use of instruments and techniques and also emphasizes the need for post endodontic rehabilitation.